Parents’ Perspectives of Children’s Emotional and Behavioural Difficulties - Abdelbasit Gadour (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2011)
There has been widespread concern about children’s emotional and behavioural difficulties (EBD) within mainstream schools in Libya. Parents’ accounts of children experiencing EBD are underrepresented in the literature, effectively giving prominence to the views and interpretations of professionals. This qualitative study used semi-structured interviews with 30 parents representing two different Libyan educational authority; this was with the intention of exploring children’s EBD and the contributing factors. Although the results echoed the generally accepted tropes, parents were not often ready to accept that their children have EBD, nor willing to attribute children’s EBD to solely individual or psychological inner conflicts. Instead, they referred children’s difficulties to a wider context in which schools and teachers contribute significantly. They maintained that mainstream schools in Libya failed to address children’s specific learning needs, reflecting deficiencies within the school system. In addition, traditional factors were found to obstruct parents from making practical contributions to children’s education, thus creating more tension and conflicts between home and school rather than solving those which already exist. The implications of this study on the attributions of EBD underline the role and responsibility of teachers leading to EBD and consequently preparing the ground for exclusion.